Optimalisasi Distribusi Singkong pada Kelompok Tani Rumpin Bogor - Gusti Ayu Made Hanny Dian Savitri (I-Com: Indonesian Community Journal, 2024)
The 33 tons of cassava harvested in Rumpin Bogor needs to be distributed properly. Rumpin Bogor Farmers Group only sells its agricultural products to middlemen at low prices and only estimates in determining the selling price of cassava. The purpose of this community service program is to increase knowledge of Rumpin Bogor Farmers Group regarding the selection of the right product distribution and considerations in determining the price of cassava. This community service and empowerment program begins with the planning phase by arranging a schedule, preparing the materials, and constructing exercises for participants. Continued with the implementation phase and closed with the evaluation phase to assess the achievement of the program. The results obtained from this program are increased knowledge and understanding regarding the right product distribution and determining competitive product prices.